BETWEEN POLICY AND PRACTICE: THE IMPLEMENTATION OF THE NATIONAL POLICY FOR INCLUSIVE SPECIAL EDUCATION IN THE STATE DEPARTMENT OF EDUCATION OF MARANHÃO (2009–2016) - de Melo Moreira, Carlos José; Ferreira, Amauri Carlos; Moreira, Verônica Lima Carneiro (Seven Editora, 2025)
This article analyzes the implementation processes of the National Policy for Special Education from the Perspective of Inclusive Education (PNEE-EI, 2008) in the State Department of Education of Maranhão (SEDUC/MA) between 2009 and 2016, through three federal programs: Inclusive Education Program: Right to Diversity, Program of Multifunctional Resource Rooms (SRM), and Accessible School Program. The study combines historical, documental, and empirical analysis to understand how national inclusive education policies were operationalized in a local context. The research adopted a qualitative approach, using policy cycle analysis, field observation, document analysis, and interviews with 25 subjects, including managers, technicians, and teachers. The results indicated that the implementation of PNEE-EI promoted significant advances, such as the expansion of enrollments of students with special educational needs (PAEE), the establishment of SRMs, and improvements in school infrastructure. However, structural, pedagogical, and cultural challenges remain, including regional inequality, insufficient resources, and gaps in teacher training. The analysis showed that inclusion is not limited to the physical presence of students in mainstream classrooms, but involves conceptual appropriation, pedagogical integration, and cultural change within schools. It was concluded that PNEE-EI constitutes a relevant instrument for the promotion of rights and the democratization of education, but its success depends on collective engagement, continuous monitoring, and adaptation to local specificities, highlighting inclusion as a historical-social process under continuous construction. DOI: https://doi.org/10.56238/sevened2025.030-071